The Astral Library : a novel - Quinn, Kate (William Morrow, an imprint of HarperCollinsPublishers, 2026)
"Alexandria 'Alix' Watson has learned one lesson from her barren childhood in the foster-care system: unlike people, books will never let you down. Working three dead-end jobs to make ends meet and knowing college is a pipe dream, Alix takes nightly refuge in the high-vaulted reading room at the Boston Public Library, escaping into her favorite fantasy novels and dreaming of far-off lands. Until the day she stumbles through a hidden door and meets the Librarian: the ageless, acerbic guardian of a hidden library where the desperate and the lost escape to new lives--inside their favorite books. The Librarian takes a dazzled Alix under her wing, but before she can escape into the pages of her new life, a shadowy enemy emerges to threaten everyone the Astral Library has ever helped protect"--